Nociceptive modulation in rats by chemical stimulation of caudate, septum and medial forebrain bundle - Macari, M.; Lico, M. C. (Elsevier, 1980)
The effects of intracerebral microinjections of Thiopental (25 μg) and Metrazol (100 μg) on the defensive motor responses elicited by nociceptive electrical stimulation of the rat's tail were determined. Also, the action of these drugs on the concentration of catecholamines in the injected areas were evaluated by the freeze-drying histofluorescence method. Albino, Holtzman rats implanted with cannulae in the caudate nucleus, medial septal area and medial forebrain bundle were used. The animals were studied following control conditions and after the drug injections. Thiopental show an antinociceptive action when injected into the medial septal area and MFB, and hyperalgesic effect when injected into the caudate nucleus. Metrazol (Pentylenetetrazol) into the medial septal area and caudate nucleus produced hyperalgesia, and analgesia when injected into the MFB. The histochemical study for catecholamines revealed decreases in DA levels in the MFB and caudate nucleus and decreases in the NA in the medial septal area after injections of both drugs. The results are discussed in terms of neuropathways and neurotransmitters involved in nociception. © 1980.
Keywords: Caudate; Chemical stimulation; Medial forebrain bundle; Nociceptive modulation; Septum